2016
DOI: 10.1002/smll.201601841
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Applications of Graphene and Its Derivatives

Abstract: Graphene materials have unique structures and outstanding thermal, optical, mechanical and electronic properties. In the last decade, these materials have attracted substantial interest in the field of nanomaterials, with applications ranging from biosensors to biomedicine. Among these applications, great advances have been made in the field of antibacterial agents. Here, recent advancements in the use of graphene and its derivatives as antibacterial agents are reviewed. Graphene is used in three forms: the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
120
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 242 publications
0
120
0
Order By: Relevance
“…Graphene, composed of a single layer of carbon atoms arranged in a hexagonal lattice, is the superstar of the 2D material family, and GMs are the most explored 2D materials for antimicrobial applications . Their sharp edges, enormous basal planes, and surface moieties endow GMs with intrinsic antimicrobial activity mainly through physical interactions with microorganisms and/or by inducing oxidative stress.…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, composed of a single layer of carbon atoms arranged in a hexagonal lattice, is the superstar of the 2D material family, and GMs are the most explored 2D materials for antimicrobial applications . Their sharp edges, enormous basal planes, and surface moieties endow GMs with intrinsic antimicrobial activity mainly through physical interactions with microorganisms and/or by inducing oxidative stress.…”
Section: Antimicrobial Activity Of Gmsmentioning
confidence: 99%
“…Herein, we categorize GM nanohybrids into two types:G M-metal and GM-metal-free nanohybrids. Recently,G Mn anohybridsf or antimicrobial applicationsh ave been summarized in several review papers, [15,21,22,24,61] and here we will briefly introduce this issue with afocusonv ery recent advancements.…”
Section: Gm Derivatives and Nanohybrids For Antimicrobial Applicationsmentioning
confidence: 99%
“…[21][22][23] For instance, graphene (and graphene oxide) has been systematically studied 24 for its antimicrobial activities, [25][26][27][28] along with its underlying molecular mechanisms. [29][30][31][32] It was revealed that graphene and graphene oxide nanosheets can cut into cell membranes, 32 extract large amount of phospholipids, 32 and create holes (pores) on cell membranes, 33 through large scale molecular dynamics simulations.…”
mentioning
confidence: 99%
“…Graphene, a monolayer of sp 2 ‐bonded carbon atoms, possesses exceptionally high mechanical strength, good thermal conductivity and unique electronic properties. Graphene and its derivatives like graphene oxide (GO), and reduced graphene oxide (rGO) are capable of inactivating bacteria regardless of light due to several possible reasons, such as wrapping, insertion of sharp edges, stress extraction and oxidative stress caused by graphene‐induced reactive oxygen species (ROS) . Graphene has remarkable potential for providing new approaches and critical thoughts in dealing with microorganism contaminations in water.…”
Section: Graphene‐based Nanocomposites For Photocatalytic Disinfectionmentioning
confidence: 99%